Real-time PCR, the best approaches for rapid testing for Mycobacterium chimaera detection in heater cooler units and extracorporeal membrane oxygenation. (September 2021) - Ditommaso, Savina; Giacomuzzi, Monica; Memoli, Gabriele; Zotti, Carla M
According to recent investigations, the risk of M. chimaera contamination of heater-cooler units (HCUs) has reached global proportions. Our aim was to field evaluate a protocol for early detection of M. chimaera contamination. We assessed the presence of viable M. chimaera in 395 water samples obtained from 48 devices (HCUs and extracorporeal membrane oxygenation) by Real Time PCR. Thirty devices were NTM positive, of which 14 were contaminated with M. chimaera . The most frequently contaminated devices were the Stockert 3T. Noteworthy, Stockert 3T devices were positive for M. chimaera. In conclusion, this study introduces novel PMA-PCR designed to specifically detect M. chimaera in HCUs and ECMO devices; this method can replace the culture method for continuous microbiological surveillance. The timely detection of M. chimaera contamination can then be used to improve effective management of the devices.